Universal Financial Crisis and Association of Southeast Asian Nations CO2 Emission - Bakhtyar, B. (International Journal of Energy Economics and Policy, 2017)
The Association of Southeast Asian Nations (ASEAN) includes 10 nations in Southeast Asia. Its population is approximately 600 million people with combined nominal GDP had grown to more than US 2.3 trillion, almost equal to the eighth largest economy in the world. Many strong economies worldwide suffered from the global financial crisis (GFC) in 2008 which resulted dipping in global CO2 emission. This study surveyed the consumption trend of petrol, coal, and natural gas as main carbon emissions in all 10 countries from 2002 to 2012. Economic growth and its effect on CO2 emission were illustrated. Although the effect of global financial economy varies in the different selected economies, the trend of CO2 emission was not dependent on gross domestic production (GDP) changes. In contrast to global emission, the 2008 GFC and the decrease in GDP did not result in the reduction of CO2 emission among ASEAN members. Keywords: CO2 emission, Major Asian Countries (MAC), Gross Domestic Production (GDP), Global Financial Crisis (GFC) JEL Classifications: F64, G01, Q4